2014
DOI: 10.4028/www.scientific.net/amr.922.137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zr Addition on Martensitic Transformation in TiMoSn Alloy

Abstract: The effects of Zr addition on martensitic transformation and the lattice parameters of α” (orthorhombic) martensite and β (bcc) phase were investigated in Ti-3mol%Mo-6mol%Sn based alloys containing up to 4mol%Zr using θ-2θ X-ray diffraction measurement (XRD) and differential scanning calorimetry (DSC). It was found by XRD that orthorhombic α” martensite phase is formed when Zr content is 0 to 2mol% while bcc β phase also existed in the alloy containing 2 to 4mol%Zr. Based on the lattice parameters in α” marten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
(21 reference statements)
2
2
0
1
Order By: Relevance
“…Then, it can be said that Zr addition to Ti-5Mo-3Sn alloys stabilizes the phase, and that the martensitic transformation temperature decreases with increasing Zr content. These are in good agreement with our previous study [16].…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations
“…Then, it can be said that Zr addition to Ti-5Mo-3Sn alloys stabilizes the phase, and that the martensitic transformation temperature decreases with increasing Zr content. These are in good agreement with our previous study [16].…”
Section: Resultssupporting
confidence: 83%
“…All the lattice parameters are listed in Table 1. It was found that the a increased with increasing Zr content, and this result was consistent with the previous study [16]. Besides, another phase such as phase was not detected.…”
Section: Resultssupporting
confidence: 81%
See 2 more Smart Citations
“…Ti-Nb, 5) TiNb Al, 6) Ti-Nb-Zr, 7) TiNbTaZr 8) and Ti-Nb-Mo 9) ), Ti-Mo base alloys (e.g. Ti-Mo-Al, 10) Ti-Mo-Sn 11) and Ti-Mo-SnZr 12) ) and Ti-Ta base alloys (e.g. Ti-Ta 13) and Ti-Ta-Sn 14) ).…”
Section: Introductionunclassified